HYBRID IMAGE PROCESSING TECHNIQUE TO DETECT PLANT DISEASE USING IOT - MAHMAD, SHARIF; JEBAKUMAR, R. (International Journal of Psychosocial Rehabilitation, 2020)
Agriculture is the foundation of economy of Indian government. There Is necessity of a great deal of creation of harvests to satisfy the need of Indian populace. In light of illnesses, huge measure of yield generation is diminished. There are different sorts of infections on the plant leaf that causes issue being developed of yields. Human eyes are less more grounded to see the leaf maladies so people don’t watch variety in the contaminated piece of leaf. These ailments some of the time may not be unmistakable to human eyes and they legitimately influencing to the harvest. The programmed ailment identification framework is utilized to programmed location and recognize the infected part on the leaf pictures and it characterize plant leaf sickness utilizing picture preparing procedures. Some significant advances are utilized for recognition like element extraction, division and grouping leaf pictures for effective infection discovery by utilizing IOT and for characterization of pictures we are utilizing the hereditary calculation.